Synthesis and antiâ€“microbial activity of 1,2,3â€“triazole tethered nitroguiacol ethers - Rachakonda, Sridhar; Naaz, Fatima; Ali, Intzar; K. R. S., Prasad; Mandava, V. Basaveswara Rao; Syed, Shafi (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Nitro aromatic/nitrophenols have been widely distributed in nature and are mostly isolated from marine microorganisms and had shown a broad spectrum of antiâ€“microbial activities against a wide range of microbial pathogens. The objective of the present work is to Synthesize some new 1,2,3â€“triazole tethered nitroguiacol ethers and evaluated of their antiâ€“bacterial and antiâ€“fungal activities. A focused library of 1,2,3-triazole tethered nitroguiacol ethers were prepared by employing Cu (I) catalyzed click chemistry reaction and evaluated for their antimicrobial activities by broth microdilution method. Among the tested compounds, compounds 8e, 8f, 8g, and 8i exhibited broadâ€“spectrum activity against selected pathogenic strains, with the MIC of 8 Âµg/mL for gramâ€“positive bacteria (StaphylococcusÂ aureus), 16 Âµg/mL for Pseudomonas aeruginosa (gramâ€“negative bacteria), and Candida species, respectively. Future investigations with this class of compounds may lead to the development of potential candidates for antimicrobial drug discovery. Â